7.6k views
4 votes
12x+6y=6 and 4y=-8x+4

User Dgp
by
4.2k points

1 Answer

3 votes

So we want to solve the system:


\begin{cases}12x+6y=6 \\ 4y=-8x+4\end{cases}

For this, we could rewrite it first:


\begin{cases}12x+6y-6=0 \\ 8x+4y-4=0\end{cases}

We could apply the elimination's method as follows:

- Multiply the second equation by -12/8:


\begin{cases}12x+6y-6=0 \\ -12x-6y+6=0\end{cases}

Notice that if we sum both equations, all terms are going to cancel each other. So, this system will have infinite solutions.

User Harish KM
by
4.5k points